Melancholy condition of the femininity and feminine creation - Natividad Corral (Arteterapia)
This paper exposed the hypothesis, based on the clinical experience, of the femininity as melancholy, as loss, devaluation and loneliness, and its consequent effects. We links this melancholy condition of femininity with feminine creation, and the importance and consequences of all this are considered for the clinical work.